The Venerable Bede’s “On the Holy Places” - Toskin Aleksandr (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This publication presents the first Russian translation of the Venerable Bede’s treatise On the Holy Places. The introductory article discusses the problem of the sources of the treatise, its purpose and its impact on the subsequent literary tradition. Close attention is given to the relationship between Bede’s On the Holy Places and the text of the same title by his older contemporary Adomndn in the context of the tradition of school theology.